Submerged and attached growth membrane bioreactors and forward osmosis membrane bioreactors for wastewater treatment - Khan, S; Hankins, N; Shen, L (Elsevier, 2016)
As an emerging technology, membrane bioreactors (MBRs) are considered to be one of the most promising wastewater treatment options in the twenty-first century for water reclamation and reuse and for meeting stringent effluent discharge standards. Membrane modules are traditionally configured as submerged units inside the bio-tank, known as submerged MBRs (SMBRs). In the recent past, the MBR process has been modified by the addition of biofilm (BF) carriers in moving or fixed bed configurations in the bioreactor, known as BF or attached growth MBR (AMBR). The AMBR combines the biologically degradative advantages of BFs with the processing efficiency of an MBR to overcome the known limitations of the SMBR. Over the past decade, research groups have focused their investigations on the AMBR, due to its superior efficiency in organic and nutrients removal and the prolonged filtration performances. Forward osmosis MBRs (FOMBRs) have also emerged quite recently, and add to MBRs two principal advantages: (1) the absence of an applied hydraulic pressure allowing a lower fouling tendency and lower energy consumption and (2) the possibility of direct water production of quality comparable to that of reverse osmosis This chapter presents an up-to-date and comprehensive review of assisted and pure BF MBR processes, examines the range of BF support media available and assesses the issues of membrane fouling, sludge characteristics and treatment performances in AMBR as compared with SMBR. It also examines the progress made to date on FOMBRs, including the types of FO membranes, the draw solutions developed and the results of process studies on water flux, fouling and water quality.